Squamous cell carcinoma in the dorsum of the tongue as a second primary tumor in oral cavity - Vendruscolo, Joana Leticia; Nogueira, Miriã Lima; Schussel, Juliana Lucena; Reksidler, Marja Cristiane; Sassi, Laurindo Moacir (Journal of Oral Diagnosis, 2020)
The squamous cell carcinoma (SCC) of the dorsum of the tongue is the less common among all SCC of the tongue. It may be misdiagnosed, because the clinical presentation can resemble other benign lesions, such as median rhomboid glossitis and lichen planus. After the treatment of an oral cancer, the risk of developing a second primary tumor (SPTs) is reported in 3-18,4% of the cases. The SPT have a significantly worse prognosis on patients with head and neck SCC. The aim of the present study is to report a case of a patient diagnosed with a SCC in the dorsum of the tongue as a second primary tumor in oral cavity. A 54-year-old man, previously diagnosed with SCC in the floor of mouth, T3N1M0 and surgically treated by surgery and adjuvant radiotherapy in 2017 was referred to the Service of Oral and Maxillofacial Surgery. He was a smoker since 18-year-old and had a history of alcohol consumption. During a follow-up examination in March 2019, a mass formation in the dorsum of the tongue was identified. Incisional biopsy was per- formed at the same day. Pathological examination of a biopsy confirmed the diagnosis of well-differentiated and invasive squamous cell carcinoma. Surgery and an adjuvant radio- therapy were performed. The report of this case aims to draw attention to the occurrence of SPT. The dorsal oral tongue is a very rare site for SCC, and patient at a younger age group must go through regular follow-up in cases of primary oral tumors, especially when the patient maintains habits such as smoke and alcohol consumption.